Renting a Home: Your Rental Agreement - Mary N. Harrison (EDIS)
Florida has laws for both the resident and landlord. This document is FCS5231-02, one of a series of the Department of Family, Youth and Community Sciences, UF/IFAS Extension. Original publication date: May 2002. Reviewed: December 2005.